Using the MMPB technique to confirm microcystin concentrations in water measured by ELISA and HPLC (UV, MS, MS/MS). (15th September 2015) - Foss, Amanda J.; Aubel, Mark T.
Abstract: Microcystins have been detected in raw and finished drinking water using a variety of techniques, including assays (immunoassay, phosphatase inhibition) and HPLC (UV, MS/(MS)). The principal challenge to microcystin analysis is accounting for the over 150 variants that have been described. A confirmatory individual variant HPLC analysis is prone to under-reporting total microcystins due to method specificity. One method that allows for total microcystin quantitation is the MMPB technique. In this study, water samples with native microcystins were oxidized to cleave the Adda moiety, common to all microcystin variants. LC-MS/MS analysis was conducted on the subsequent MMPB (3-methoxy-2-methyl-4-phenylbutyric acid) molecule and calibrated using a certified reference standard (microcystin-LR) and 4-phenylbutyric acid. Total microcystin concentrations from MMPB were compared to Adda ELISA and individual variant analyses (LC-UV, LC-MS/(MS)). Variants of microcystin, including [DAsp 3 ]MC-RR, [Dha 7 ]MC-RR, MC–RR, MC-YR, MC-LR, [DAsp 3 ]MC-LR, [Dha 7 ]MC-LR, MC-WR, MC-LA, and MC-LY were detected and quantified in samples. The individual variant analyses did not account for total microcystins present in samples, as indicated by ELISA and MMPB data. Results demonstrated the MMPB technique is a simple and valuable approach to confirm ELISA data when analyzing microcystins, with method detection limits of 0.05 μg L −1 for total microcystins. Highlights: Raw and Finished water samples were analyzed for microcystins. Preparation techniques of raw water using sonication and freeze thaw were compared. ELISA data was compared to LC-MS, LC-UV, LC-MS/MS and the MMPB method. Multiple variants of microcystins were detected. Individual variant analyses did not account for all MCs measured by ELISA & MMPB.